Evergreen agriculture - Garrity, Dennis P. (World Agroforestry Centre, 2014)
Presentation by Dennis Garrity, World Agroforestry Centre (ICRAF) at the Global Forum for Innovations in Agriculture (GFIA), February 4, 2014